Identification of important factors for implementation of TQM in Indian SMEs in context of Vidarbha and Khandesh region. (1st January 2013) - Kalpande, Shyamkumar D.; Gupta, R.C.; Dandekar, Milind D.
The paper attempts to identify weight of critical success factors (CSFs) for the successful implementation of total quality management (TQM) in small and medium enterprises (SMEs) in Vidarbha and Khandesh region in India. The study first investigates the critical factors and sub-factors that determine the adoption and successful implementation of TQM. Moreover, the evaluation weights are determined using analytic hierarchy process (AHP). The findings advocate that these enterprises would stress the basic TQM factors of organisation and 'understanding of customer needs (CN)', 'common understanding of quality (UQ)' and 'use of team process (TP)' are the most important factors. The results suggest a generic hierarchy model for organisations to prioritise the critical factors and formulate strategies for implementing TQM in Vidarbha and Khandesh, as well as other cities and regions in India.